2022
DOI: 10.1007/s00417-022-05700-y
|View full text |Cite
|
Sign up to set email alerts
|

Visual and optical quality of enhanced intermediate monofocal versus standard monofocal intraocular lens

Abstract: Purpose Intraocular lens designs are constantly evolving, trying to obtain more spectacle independence after cataract surgery. This advantage can be linked to some disadvantages, such as optical quality decrease. For that reason, it is important to assess, not only the amount of vision provided but also the quality of vision once they are implanted. The purpose of the present work was to compare the visual performance between two monofocal intraocular models: a standard model and a monofocal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Regarding the laboratory evidence, the elevation changes for refractive EDoF lenses were not achieved for Table 5 Criteria accomplished by the enhanced monofocals according to the ANSI standard definition of EDOF lenses and additional points RCT Randomized clinical trial, CS Case series ANSI-1: Statistical significance versus control for mean monocular visual acuity, with distance correction, at an intermediate distance of 66 cm ANSI-2: An increase in depth of field is achieved in the monocular defocus curve with distance correction equal to or greater than 0.5 D for a visual acuity level of 0.2 logMAR ANSI-3: The median monocular visual acuity, with distance correction, at an intermediate distance of 66 cm, is at least 0.2 logMAR ANSI-4: Monocular acuity at distance, with correction at this distance, is statistically non-inferior to control using a non-inferiority margin of 0.1 logMAR Add-1: Statistical significance versus control for mean binocular visual acuity, with distance correction, at an intermediate distance of 66 cm Add-2: An increase in depth of field is achieved in the binocular defocus curve with distance correction equal to or greater than 0.5 D for a visual acuity level of 0.2 logMAR Add-3: The mean monocular visual acuity, with distance correction, at an intermediate distance of 66 cm, is at least 0.2 logMAR Add-4: Starting with CDVA, the monocular defocus range at 0.2 logMAR is ≥ 1.5 and < 2. Bova et al [44], Nanavaty et al [39], Corbelli et al [49], Lopes et al [40], Steinmüller et al [17], Auffarth et al [45], Ucar et al [37], Kang et al [41], Unsal et al [38], Cinar et al [42], Huh et al [28], Yangzes et al [36], Eguileor et al [43], Mencucci et al [3], Garzón et al [46] the Tecnis Eyhance [31,32], and the optical quality studies that included both, enhanced monofocals and EDoF lenses, showed a higher depth of focus range with poorer distance optical quality for EDoF lenses in comparison to enhanced monofocals [25,27]. These laboratory results were in agreement with clinical evidence of studies including enhanced monofocals and EDoF lenses, demonstrating a higher range of focus and better DCNVA for the latter [33][34][35]49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the laboratory evidence, the elevation changes for refractive EDoF lenses were not achieved for Table 5 Criteria accomplished by the enhanced monofocals according to the ANSI standard definition of EDOF lenses and additional points RCT Randomized clinical trial, CS Case series ANSI-1: Statistical significance versus control for mean monocular visual acuity, with distance correction, at an intermediate distance of 66 cm ANSI-2: An increase in depth of field is achieved in the monocular defocus curve with distance correction equal to or greater than 0.5 D for a visual acuity level of 0.2 logMAR ANSI-3: The median monocular visual acuity, with distance correction, at an intermediate distance of 66 cm, is at least 0.2 logMAR ANSI-4: Monocular acuity at distance, with correction at this distance, is statistically non-inferior to control using a non-inferiority margin of 0.1 logMAR Add-1: Statistical significance versus control for mean binocular visual acuity, with distance correction, at an intermediate distance of 66 cm Add-2: An increase in depth of field is achieved in the binocular defocus curve with distance correction equal to or greater than 0.5 D for a visual acuity level of 0.2 logMAR Add-3: The mean monocular visual acuity, with distance correction, at an intermediate distance of 66 cm, is at least 0.2 logMAR Add-4: Starting with CDVA, the monocular defocus range at 0.2 logMAR is ≥ 1.5 and < 2. Bova et al [44], Nanavaty et al [39], Corbelli et al [49], Lopes et al [40], Steinmüller et al [17], Auffarth et al [45], Ucar et al [37], Kang et al [41], Unsal et al [38], Cinar et al [42], Huh et al [28], Yangzes et al [36], Eguileor et al [43], Mencucci et al [3], Garzón et al [46] the Tecnis Eyhance [31,32], and the optical quality studies that included both, enhanced monofocals and EDoF lenses, showed a higher depth of focus range with poorer distance optical quality for EDoF lenses in comparison to enhanced monofocals [25,27]. These laboratory results were in agreement with clinical evidence of studies including enhanced monofocals and EDoF lenses, demonstrating a higher range of focus and better DCNVA for the latter [33][34][35]49].…”
Section: Discussionmentioning
confidence: 99%
“…Three clinical studies compared enhanced monofocals with EDoF lenses, [33][34][35] 14 compared the clinical results with a standard monofocal, [3,17,28,[36][37][38][39][40][41][42][43][44][45][46] and three case series without a comparison group were identified [16,47,48] Only one study included both monofocal and EDoF lenses in comparison to Tecnis Eyhance [49]. Supplemental file B contains all the data extracted from clinical studies.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it allows greater independence from spectacles in day-to-day activities, such as window shopping and playing board games, and when using electronic devices, such as PCs, iPads, and cell phones, which are increasingly used by patients undergoing cataract surgery. 10,13 Although there are several retrospective, observational case series and case-control studies that compare the enhanced and conventional monofocal IOLs, there are only a few randomized comparative prospective studies. 1,3,4,[8][9][10][11][13][14][15][16] These do not assess patient satisfaction and the presence of positive dysphotopsias.…”
mentioning
confidence: 99%
“…10,13 Although there are several retrospective, observational case series and case-control studies that compare the enhanced and conventional monofocal IOLs, there are only a few randomized comparative prospective studies. 1,3,4,[8][9][10][11][13][14][15][16] These do not assess patient satisfaction and the presence of positive dysphotopsias. Thus, the main aim of this randomized clinical trial was to assess the primary endpoints of binocular intermediate and distance visual acuity and secondary endpoints that included patient satisfaction and positive dysphotopsias.…”
mentioning
confidence: 99%